1993
DOI: 10.1002/humu.1380020506
|View full text |Cite
|
Sign up to set email alerts
|

Single-strand conformation polymorphism (SSCP) analysis of the molecular pathology of hemophilia B

Abstract: In the present study, we report the application of polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) analysis to the screening of seven functionally important factor IX gene (FIX) regions (total length 2.66 kb) in 9 unrelated haemophilia B patients of Portuguese or African origin. In eight of the patients an altered migration pattern of single-stranded DNA was observed. Direct sequencing of the relevant DNA fragments unveiled the following sequence alterations: two novel mutations, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The G -82 to T base substitution in intron 2, already described by us (David et al, 1993), was found in a second patient of African origin. Allele-specific amplification analysis of 162 independent X chromosomes from Portuguese (98) and African black (64) populations, allowed us to establish the frequency of the dimorphic T allele as 4.7%, unique to the African black population.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The G -82 to T base substitution in intron 2, already described by us (David et al, 1993), was found in a second patient of African origin. Allele-specific amplification analysis of 162 independent X chromosomes from Portuguese (98) and African black (64) populations, allowed us to establish the frequency of the dimorphic T allele as 4.7%, unique to the African black population.…”
Section: Resultssupporting
confidence: 62%
“…DNA preparation, amplification by polymerase chain reaction (PCR), SSCP analysis, and direct sequencing were carried out essentially as described by David et al (1993David et al ( , 1994. (Annealing temperatures for the co-amplification of different fragments and oligonucleotides used are available from the authors on request.)…”
Section: Dna Amplification and Sscp Analysismentioning
confidence: 99%
“…The formation of a Moebius loop-like structure during DNA replication may serve as an intermediate which potentiates the insertion. We have observed a similar sequence structure in the case of a 9 bp insertion in the FIX gene (28). Alternatively, a mechanism based on slipped mispairing and resynthesis of the 7 bp sequence could also explain this duplication.…”
Section: Discussionsupporting
confidence: 64%
“…Segregation of X chromosomes were studied using polymorphisms in the FIX ( Hin fI in intron A and Mnl I in exon VI) and FVIII ( Bcl I in intron 18, Xba I in intron 22) genes and at the DXS52 locus ( Bcl I) by Southern blot analysis or polymerase chain reaction (PCR), performed as previously described [13,14].…”
Section: Chromosome Segregation and Methylation Analysismentioning
confidence: 99%